Peran Strategis Supervisi Pendidikan dalam Pengembangan Mutu Lembaga Pendidikan - Nida Nur Aisyah; Awwal Muzakki Alkautsar (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the strategic role of educational supervision in improving the quality of Islamic educational institutions through three key aspects: enhancing teacher competence, strengthening institutional management, and fostering a culture of quality. Using a qualitative method with a literature study approach, this research demonstrates that both instructional and administrative supervision contribute significantly to the development of professionalism and institutional quality. Supervision functions not only as a monitoring activity but also as a continuous guidance process that reinforces the quality of learning and institutional governance. Keywords: educational supervision, quality of Islamic education, institutional management, teacher competence, quality culture